Northeast First Nation participation in the British Columbia oil and gas policy community - Wolsey, Tracey Marie (Author); Poelzer, Greg (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2001)
This thesis investigates the changing role of First Nations in the oil and gas policy community in northeastern British Columbia. Prior to the NDP government coming to power in the early 1990s and prior to some important court cases, First Nation communities were not members of the policy community. As a result of these two critical variables--important court cases and NDP government policy--the thesis argues that the First Nation communities in northeast British Columbia are now members of the oil and gas policy community. This critical power shift has resulted in changes to policy, changes to oil and gas development, and changes to the way the provincial government, oil and gas companies and the First Nation communities interact with each other. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1220353